Analisis Faktor Penyebab Dan Dampak Bullying Verbal Di SDN Inpres 2 Tanamodindi Palu - Siti Nurhalisa; Nurwahyuni Nurwahyuni; Nur Eka Wahyuningsih Riyadi (Jurnal Ilmiah Dikdaya, 2026)
Verbal Bullying  represents a prevalent form of violence in elementary schools that demands serious attention due to its detrimental effects on student development. This research analyzes the causal factors of verbal Bullying  from student, teacher, and school environment perspectives, while examining its social and academic impacts on students at SDN Inpres 2 Tanamodindi Palu. The research employed a qualitative approach with a case study design. Six informants were selected through purposive sampling: two victim students, two perpetrator students, one witness student, and one fifth-grade teacher. Data collection utilized participatory observation, in-depth interviews, and documentation, with thematic analysis applied to examine the findings. Results reveal that verbal Bullying  encompasses four primary dimensions: individual factors (recognition-seeking behavior, low empathy, and superiority complex), family factors (ineffective communication patterns and weak parent-child relationships), school factors (inadequate teacher supervision and insufficient prevention programs), and peer factors (group reinforcement and negative behavior transmission across grade levels). The impacts of verbal Bullying  are multidimensional, affecting psychological dimensions (shame, fear, sadness, and internalization of negative labels), academic performance (reduced motivation and achievement), and social functioning (isolation, defensive social strategies, and school avoidance). Notably, Bullying  witnesses also experience emotional distress, suggesting the development of collective trauma within the school environment.